Axiological Content of Management Innovations - Marmaza, Oleksandra (Pedagogical Discourse, 2021)
The paper notes that the peculiarity of the management activities of the head of the educational institution at the present stage is determined by the emergence of innovative leadership technologies, and innovations have their unique significance for each head, team, institution as a whole. In accordance with the set goal (to reveal the axiological principles of management innovations) it is substantiated that it is expedient to consider management innovations in axiological content – from the point of view of their value. It is determined that managerial innovations can relate to the content of activities, forms, methods, procedures, technologies and management techniques. The definition of innovative management of an educational institution is a specific purposeful activity that involves the application of new content, testing the effectiveness of creative management decisions, updated management principles, modernized functions, new technologies and techniques, optimized organizational structures, management systems or their components, methods and forms of activities. Using the methods of scientific cognition, the axiological content of innovations in the management of an educational institution is revealed, which should be an indicator of readiness and ability of a head to unconventionally solve current problems and evidence of high professionalism and innovative competence. Determining the values of management innovations due to their importance is productive, as it allows in theoretical and practical aspects to consider the axiology of a particular innovation in terms of its relationship with the head, staff, features of the educational institution. The axiological potential of innovations is shown on the example of participatory management and coaching. Criteria of management innovations in axiological content and approaches to estimation are defined.